THE EFFECT OF HEALTH EDUCATION USING THE PEER GROUP DISCUSSION METHOD ON DIETARY COMPLIANCE AND ORAL ANTI-DIABETIC MEDICATION IN PATIENTS WITH DIABETES MELLITUS AT THE FATUKANUTU PUBLIC HEALTH CENTER, KUPANG REGENCY - Fransiskus S.Onggang; Aben B.Y.H Romana; Bringiwatty Batbual; Gadur Blasius; Simon Sani Kleden; Dominggos Gonsalves; Oklan OBT Liunokas (Jurnal Cakrawala Ilmiah, 2025)
Diabetes Mellitus can occur in all age and socioeconomic strata. The number of metabolic diseases worldwide has increased by 25.0%. This study aimed to examine the effect of health education using peer group discussions on dietary adherence and oral antidiabetic medication intake in diabetes mellitus patients at the Fatukanutu Community Health Center, Kupang Regency. The research design used in this study was a one-group pre-post test design. The aim was to determine the effect of health education using peer group discussions on dietary adherence and oral antidiabetic medication intake in diabetes mellitus patients at the Fatukanutu Community Health Center, Kupang Regency. The independent variable in this study was the provision of health education using peer group discussions on the diabetes diet and taking antidiabetic medication, while the dependent variable was the dietary adherence of diabetes mellitus patients and taking antidiabetic medication at the Fatukanutu Community Health Center, Kupang Regency. The sample size was 44 people. Results: The results of the study showed that most of the respondents were male (52.3%), aged over 55 years (54.5%), had a junior high school education (50.0%) and worked as self-employed (27.3%) and retired (27.3%). The Level of Diet Compliance and Taking Oral Anti-Diabetic Medication in Diabetes Mellitus Patients at the Faukanutu Health Center, Kupang Regency Before Health Education Method Peer Group Discussion. The results of the study before the implementation of the intervention showed that most of the respondents (75%) did not comply with dietary compliance and most of the respondents (84.1%) did not comply with medication compliance. The Level of Diet Compliance and Taking Oral Anti-Diabetic Medication in Diabetes Mellitus Patients at the Fatukanutu Health Center, Kupang Regency After Health Education Method Peer Group Discussion. The results of the study after the implementation of the intervention showed that most of the respondents (81.8%) complied with dietary compliance and most of the respondents (79.5%) complied with medication compliance. The Effect of Health Education Using Peer Group Discussion on Diet Compliance and Oral Antidiabetic Medication in Diabetes Mellitus Patients at the Fatukanutu Community Health Center, Kupang Regency. Conclusion: Based on the Wilcoxon test results with a p-value of 0.000 (<0.05), it can be concluded that the health education intervention using peer group discussion has an effect on improving dietary compliance and medication adherence in diabetes mellitus patients at the Fatukanutu Community Health Center, Kupang Regency